The Influence of Consumer Knowledge and Product Quality Perception on Korean Beauty Product Purchase Decisions - Aprilina Putri; Nur Ahmadi Bi Rahmani; Maidalena Maidalena; Saidina Putri (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2023)
This study examines the relationship between the foreign brand halo effect and beauty consciousness on self-brand connection in beauty consumption. The research also investigates the moderating role of age in this relationship. Data were collected through an online survey focusing on two beauty brands from South Korea (K-beauty). The results of this study contribute to the literature on consumer-brand relationships and international marketing. There were no differences between young adult female consumers and more mature adult female consumers in the influence of beauty consciousness on self-brand connection. However, there were substantial differences between the two consumer groups in the influence of the foreign brand halo effect on self-brand connection. Additionally, the halo effect showed the greatest impact on the willingness to pay more. Consumers are also willing to pay more for brands from countries with a positive image..